ANALISIS KEUNTUNGAN DAN NILAI TAMBAH AGROINDUSTRI KUE BEPANG PADA UD. CIPUT DI DESA KARONDORAN KECAMATAN LANGOWAN TIMUR (Profit Analysis and Added value of Cake bepang Agroindustry at UD. Ciput in Karondoran Village, East Langowan Sub District) - Gricsellah P. Kalangie; Agnes Estephina Loho; Paulus Adrian Pangemanan (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The objective of this study is to analyze the profit and added value of the Cake Bepang Agroindustry at UD. Ciput in Karondoran Village, East Langowan Sub District. This research was conducted in May 2021. The data collected used in this study namely primary data and secondary data.  Primary data  was obtained  through direct interviews with respondents by  using a list of questions (questionnaires).The research results showed that the profit per production process of the Cake Bepang Agroindustry at UD. Ciput in Karondoran Village  was obtained  total revenue of Rp. 875,000 and a total cost of Rp. 632,283, the profit generated was Rp. 242,717. Revenue is obtained from the total production of 70 packs with a price per unit of Cake Bepang Rp.12,500/pack, and the total cost by adding up fixed costs Rp.260,833 with variable costs Rp.371,450. For the results of the added value per production process of Rp.592,717, the value-added ratio of 48.39%, the margin obtained was Rp.1.135,000. And for other input contributions was Rp.542.283.